Answer:
Option c. (2,0)
Explanation:
(1) 4x-2y=8
(2) 2x-4y=4
Using the method of elimination: Multiplying the second equation by -2:
(2) -2(2x-4y)=-2(4)
Applying the distributive property:
-2(2x)-2(-4y)=-8
-4x+8y=-8
Adding this equation with the first equation:
-4x+8y+4x-2y=-8+8
6y=0
Solving for "y": Dividing both sides of the equation by 6:
6y/y=0/6
y=0
Replacing y=0 in the second equation:
(2) 2x-4(0)=4
2x-0=4
2x=4
Solving for "x": Dividing both sides of the equation by 2:
2x/2=4/2
x=2
The solution is (x,y)=(2,0)